2019
DOI: 10.1039/c9cc06797c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of sub-10 nm-sized bright red-emitting upconversion nanophosphors via tetrahedral YOF:Yb,Er seed-mediated growth

Abstract: Sub-10 nm-sized bright red-emitting YOF:Yb,Er/YOF core/shell upconversion nanophosphors are successfully synthesized from ultrasmall tetrahedral-shaped YOF:Yb,Er cores with well-defined crystallographic facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…11 Although several studies on red-emitting UCNPs were reported, 18,29−31 to the best of our knowledge, research on size-controlled synthesis of the red-emitting UCNPs and ultrasmall red-emitting UCNPs with sub-10 nm core size is rare. 32 In particular, for strong red-emitting NaErF 4 -based UCNPs which showed stronger UCL than previously reported red-emitting UCNPs, a strict synthetic condition for the formation of the hexagonal structure makes the synthesis of sub-10 nm NaErF 4 -based core UCNPs difficult. 24 On the other hand, it was reported that tetragonal-structured rare-earth (RE)-doped LiYF 4 -based UCNPs show strong ultraviolet (UV), blue, and green UCL.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…11 Although several studies on red-emitting UCNPs were reported, 18,29−31 to the best of our knowledge, research on size-controlled synthesis of the red-emitting UCNPs and ultrasmall red-emitting UCNPs with sub-10 nm core size is rare. 32 In particular, for strong red-emitting NaErF 4 -based UCNPs which showed stronger UCL than previously reported red-emitting UCNPs, a strict synthetic condition for the formation of the hexagonal structure makes the synthesis of sub-10 nm NaErF 4 -based core UCNPs difficult. 24 On the other hand, it was reported that tetragonal-structured rare-earth (RE)-doped LiYF 4 -based UCNPs show strong ultraviolet (UV), blue, and green UCL.…”
Section: Introductionmentioning
confidence: 93%
“…Although we previously reported sub-10 nm red-emitting YOF:Yb,Er/YOF C/S UCNPs, it was difficult to control the size of the YOF:Yb,Er because a uniform morphology was achieved under specific synthetic conditions. 32 Here, we finely tuned the size of the LiErF 4 -based red-emitting UCNPs from ∼3 to 10 nm within 10 nm range. By systematically adjusting the size and shell thickness, strong red UCL could be realized from ultrasmall red-emitting UCNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, early diagnosis of cancer cells has attracted intensive concerns to prevent the terrible damage of this serious disease. , Fluorescence imaging is an important imaging method especially when the diagnosis and treatment were under a single irradiation source. Compared with traditional medical imaging techniques (X-ray, CT, MRI, ultrasound, etc . ), fluorescence imaging can noninvasively detect abnormalities in subcellular, cellular, and even molecular levels in the course of disease with the advantages of simplicity, high sensitivity, and high spatial resolution. Conventional down-conversion fluorescent probes are excited by ultraviolet light, and the excitation light always faces the problem of being absorbed by the tissue. Alternatively, the up-conversion luminescence is excited by the near-infrared (NIR) light which is located in the bio-optical window with lower autofluorescence. It seems the bioapplication of up-conversion luminescence (UCL) in fluorescence imaging is more advantaged, especially for the red UCL emission (600–700 nm) under the NIR excitation (700–1000 nm). However, UCL bioimaging is limited in application due to its low energy transfer efficiency, insufficient intensity, and low penetration depth. Four main strategies have been proposed to improve the UCL efficiency including adjusting the crystal shape and size, codoping metal or alkalis ions, design of core–shell structure, and introducing the surface plasmon resonance. During these methods, tuning the doping metallic ions and the proportion are the common strategies to improve the luminescence intensity. However, the traditional “trial and error” method relies on a large number of experiments, time, and resources with different parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles have the potential to be used in diverse applications such as biomedicine, data storage, solar energy conversion (Chen et al, 2015 , 2019 ; Tsang et al, 2015 ; Zhou B. et al, 2015 ; Qi et al, 2017 ; Su et al, 2017 ; Zhu et al, 2017 ; Chen B. et al, 2018 ; Chen S. et al, 2018 ; Gai et al, 2018 ; Zheng et al, 2018 ; Ma et al, 2019 ). Particularly, the growing demand of lanthanide-doped nanoparticles using in various applications has in turn greatly stimulated basic research to develop novel nanoparticles with controlled size, shape, phase and desired properties (Wang et al, 2010 , 2019 ; Du et al, 2016 ; Liu D. et al, 2016 ; Shi et al, 2017 ; Kang et al, 2019 ; Sun et al, 2019 ; Wang, 2019 ; Wu et al, 2019 ; Zhao et al, 2019 ; Zheng et al, 2019 ; Chen and Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%